POTENSI DATA RADAR SATELIT SENTINEL-1 DALAM PENGUJIAN KEKASARAN PERMUKAAN DAN KELEMBABAN TANAH UNTUK PEMANTAUAN FASE PERTUMBUHAN TANAMAN PADI (STUDI KASUS : INDRAMAYU, JAWA BARAT) - Alifiyanti, Hana
Active radar systems can analyze an object on the Earth surface using backscatter. The backscattering value is influenced by the characteristics of the object, including the surface roughness and the dielectric constant which is influenced by the water content of the object so it can be used to estimate the value of soil moisture. Acquisition of radar system is not affected by weather conditions and the penetration of clouds is better because Synthetic Aperture Radar (SAR) uses microwaves, considering that Indonesia is included in a tropical climate so that the cloud cover contained in the atmosphere is quite a lot. The study was conducted in Indramayu Regency, West Java using radar Sentinel-1 Satellite imagery. The method used in this study is semi-empirical, using a model from Campbell and Shepard (1996) that has been modified in the calculation of surface roughness and a modification of the model from Dubois (1995) to calculate the dielectric constant that used to estimate soil moisture. The results show that the surface roughness model formed can be related to the rice growth phase with RMSE of 1.1899 and 0.8970, and RMSE of soil moisture models of 0.438 and 0.430.